UGI Bleed- A Rare Presentation of Carcinoma Gall Bladder with Cholecystoduodenal Fistula - Karishma Das; Swarup Kar; Usha Rani Pegu; Liza Hazarika (Assam Journal of Internal Medicine)
Upper GI bleeding(UGIB) is defined as bleeding derived from a source proximal to the ligament of Treitz. It is a life threatening condition. Bilioenteric fistulas are abnormal communication between the bile duct system and the gastrointestinal tract that occurs spontaneously and usually occurs as a rare complication of untreated gallstone in majority of cases. Cholecystoduodenal fistula(CDF) as a cause of upper GI bleeding is an extremely rare event. It has been theorized that a cholecystoduodenal fistula may lead to development of carcinoma gall bladder due to chronic reflux of duodenal contents. High index of clinical suspicion is required to make a diagnosis.